Lipolysis profile of some non-European raw milk cheese varieties: a review - Aikaterini GEORGALA (Acta Agriculturae Slovenica)
This review focuses on the lipolysis profile of some non European raw milk cheese varieties. Lipolysis data of some traditional/artisanal non-European raw milk cheeses such as cheeses ripened in an animal skin, cheeses ripened in brine, cheeses produced in small scale by local dairies etc., are collected and presented in this study. The main characteristics of these cheeses and their lipolysis profile in general are discussed. Factors such as the type of cheese, the technology applied for cheese making and the age of cheese are shown to influence the lipolysis profile.